PENERAPAN PENDIDIKAN KARAKTER DALAM MENINGKATKAN KETERAMPILAN SOSIAL DAN ETIKA SISWA PADA PRAKTIKUM BIOLOGI DI LABORATORIUM MAN SIMALUNGUN - syukrhaini, dyla; Herni, Zulfiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the application of character education in improving students' social skills and ethics in biology practicum at MAN Simalungun laboratory. This study uses a qualitative descriptive approach with phenomenological method to understand students' experiences and perceptions of character education. Data were collected through in-depth interviews, observations, and document analysis. The results show that character education can shape students' positive character and improve their social skills and ethics, such as cooperation, responsibility, and respecting others' opinions. This study also shows that character education can increase students' awareness of the importance of ethics and morals in daily life.